2019
DOI: 10.1002/eat.23036
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and responding to child maltreatment when delivering family‐based treatment—A qualitative study

Abstract: Introduction This study describes practitioner strategies, perceptions, experiences with identifying and responding to child emotional abuse (CEA) and child exposure to intimate partner violence (CEIPV) when providing Family‐Based Treatment (FBT) to children and adolescents with eating disorders. Method Using qualitative interpretive description, this study recruited a purposeful sample of practitioners (N = 30, 90% female) implementing FBT for adolescent eating disorders. Semi‐structured interviews focused on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…A qualitative study with nurses identified that power battles over 'punitive' feeding causes patients great anguish and can rupture the therapeutic alliance [64]. These interactions may be overlooked as a complicating feature within family-based treatment [65]. Interestingly, in adolescence, reduced extinction of fears appears to be more pronounced with co-morbid depression [66].…”
Section: Behavioural Consequences Of Anorexia Nervosamentioning
confidence: 99%
“…A qualitative study with nurses identified that power battles over 'punitive' feeding causes patients great anguish and can rupture the therapeutic alliance [64]. These interactions may be overlooked as a complicating feature within family-based treatment [65]. Interestingly, in adolescence, reduced extinction of fears appears to be more pronounced with co-morbid depression [66].…”
Section: Behavioural Consequences Of Anorexia Nervosamentioning
confidence: 99%
“…These clinician narratives highlight some key areas to bridge this research-practice gap that include:The establishment of more comprehensive guidelines and ongoing assessment of “the appropriateness and efficacy of FBT(-AN)” ([46], p., 298) in therapeutic contexts including for example, when:The adolescent’s emotional distress (including in their eating and weight restoration) is too great and the intervention risks being traumatising;The burden on a family is too great and what might be the next steps in the care of the adolescent and their family; andThere exists a risk of child emotional abuse and family violence, thus highlighting the need for therapists who practice FBT-AN to have comprehensive training in responding to child emotional abuse and family violence [46]. Drawing on therapist expertise to both inform clinical practice guidelines [25] and future research into how to effectively tailor manualised treatments to the adolescent and family needs and preferences through reflective practice in supervision [43].…”
Section: Discussionmentioning
confidence: 99%
“…The establishment of more comprehensive guidelines and ongoing assessment of “the appropriateness and efficacy of FBT(-AN)” ([46], p., 298) in therapeutic contexts including for example, when:The adolescent’s emotional distress (including in their eating and weight restoration) is too great and the intervention risks being traumatising;The burden on a family is too great and what might be the next steps in the care of the adolescent and their family; andThere exists a risk of child emotional abuse and family violence, thus highlighting the need for therapists who practice FBT-AN to have comprehensive training in responding to child emotional abuse and family violence [46]. …”
Section: Discussionmentioning
confidence: 99%
“…A recent qualitative meta-synthesis highlighted that healthcare and social service providers experience challenges related to recognizing and responding to child maltreatment in their practice (27). Emerging work suggests that this is also the case among ED specialists (28). There are several potential implications of this practice challenge.…”
Section: Recognizing Child Maltreatment Within the Therapeutic Stancementioning
confidence: 99%
“…These include a non-determinant view of the illness, a non-authoritarian therapeutic stance, empowerment of caregivers to facilitate the recovery process, as well as an initial prioritization on nourishment and symptom interruption ( 34 – 36 ). In the context of FBT, an unequivocal belief that caregivers are a positive resource to their child’s recovery has the potential to negate the identification of adverse caregiver behavior in the context of a child’s physical and psychological vulnerability, as well as magnify the impacts of any ongoing child maltreatment ( 28 ). Second, a non-determinant view of the illness may implicitly suggest to practitioners that attending to the relational patterns in the family system is secondary to the emphasis on symptom interruption.…”
Section: Recognizing Child Maltreatment Within the Therapeutic Stancementioning
confidence: 99%